Double gastric neoplasm: Total gastrectomy - Mazza Bruno, Milton E.; Lopez, Julio; A. Pravia, Juan (Cirugía del Uruguay, 1971)
An extremely rare case of double gastric carcinoma was treated with good immediate results through total gastrectomy and esophago-duodenal anastomosis in one.